2005
DOI: 10.1007/s00261-005-0313-9
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of hepatocellular carcinoma with complete necrosis: case report

Abstract: Spontaneous regression of hepatocellular carcinoma is rare phenomenon. A 74-year-old man was found to have a hepatocellular carcinoma with intrahepatic metastases in the lateral segment of the liver. Before surgery, he developed severe cholangitis due to choledocholithiasis and was treated endoscopically. The tumor marker level decreased markedly, and hepatectomy was performed. The resected tumor demonstrated complete necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…[56][57][58][59] In a report, the absolutely count of peripheral blood lymphocyte in the early postoperative period was significantly decreased in patients who underwent intra-operative blood transfusion compared to that in those who did not. 21 Concerning the mechanism of immunosuppressive effect of blood transfusion, it has been reported that soluble HLA class I molecules and soluble Fas-ligand released by leukocytes present in blood products inhibit the activity of NK cells and cytotoxic T cells, which are known to reduce immune capacity and, therefore, may predispose to postoperative infections.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58][59] In a report, the absolutely count of peripheral blood lymphocyte in the early postoperative period was significantly decreased in patients who underwent intra-operative blood transfusion compared to that in those who did not. 21 Concerning the mechanism of immunosuppressive effect of blood transfusion, it has been reported that soluble HLA class I molecules and soluble Fas-ligand released by leukocytes present in blood products inhibit the activity of NK cells and cytotoxic T cells, which are known to reduce immune capacity and, therefore, may predispose to postoperative infections.…”
Section: Discussionmentioning
confidence: 99%
“…Local factors may be involved, such as an excessively rapid growth of the neoplasm in a cirrhotic liver with insufficient vascular flow, 5 thrombotic occlusion of the arterial vessels supplying the neoplasm, 6 increased immune response on the part of the patient, 7 and/or an episode of severe cholangitis caused by choledo- cholithiasis. 8 In our patient, nodular necrosis was incidentally revealed 4 weeks after sonographically guided needle biopsy, which may have triggered it through intranodular hemorrhage.…”
Section: Discussionmentioning
confidence: 92%
“…The neoplastic tissue is more sensitive than normal tissue to a sudden reduction of the blood and oxygen supply because of its high metabolic requirements [12]. A systemic inflammatory response includes cholangitis, sepsis, and trauma [13, 14]. Huz et al [15] also suggested that the spontaneous regression of HCC is most commonly associated with tumor hypoxia or a systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%